An Efficient Approach to Task Scheduling in Computational Grids - Sadasivam, G Sudha; Rajendran V, Viji (INFOCOMP Journal of Computer Science, 2010)
Resource management in a grid environment is complex. Scheduling strategy plays an important role in the grid environment to schedule the user jobs, and dispatch them to appropriate grid resources. A good task scheduling method is essential to reduce the total time taken for job execution in the grid. In a grid environment, the jobs are processed at the grid resources in a fine-grained form that results in a low computation-communication ratio. So an efficient job grouping-based scheduling system is required to dynamically assemble the individual fine-grained jobs of an application into a group of jobs and then transmit these coarse-grained jobs to the grid resources. The objective of this paper is to develop a scheduling strategy using job groups that optimizes the utilization of processing capabilities of grid resource and reduces the total time taken to process user jobs.